AAC Peace River field pea - Bing, Deng-Jin; Beauchesne, Don; McLaren, Debra; Vera, Cecil; Gehl, David (Canadian Journal of Plant Science, 2013)
Bing, D. J., Beauchesne, D., McLaren, D., Vera, C. and Gehl, D. 2013. AAC Peace River field pea. Can. J. Plant Sci. 93: 337–339. AAC Peace River is a semi-leafless, yellow cotyledon field pea (Pisum sativum L.) cultivar developed at Agriculture and Agri-Food Canada, Lacombe Research Centre, Lacombe, Alberta, Canada. It is an early-maturing cultivar and is resistant to powdery mildew caused by Erysiphe pisi Syd. AAC Peace River is adapted to all field growing regions in western Canada, and is especially suited to regions with short growing seasons.